Understanding Entrepreneurial Intention: The Prediction of Entrepreneurial Behavior - Kusumawijaya, Ida Ketut (International Review of Management and Marketing, 2020)
This study examines the predictive ability of entrepreneurial behavior towards entrepreneurial intention star hotel employee in Bali. Assessing self efficacy in predicting entrepreneurial intention. Review the predictions of self-determination on entrepreneurial intention. Assessing self identity in predicting entrepreneurial intention. The Entrepreneurial behavior referred to from Kirkley (2016) research, consists of dimensions of self efficacy, self-determination, self identity. For entrepreneurial intention refer to Dinis et al. (2013) research. Entrepreneurial behavior in decision making is related to the assessment process and thinking by identifying and integrating knowledge, autonomy, competence and desire in order to achieve the entrepreneurial intention goals. This research was conducted on star hotel employees in Bali with 156 respondents. The questionnaires returned were 156 with a response rate of 100%. Each research instrument uses a 5 Likert scale measurement. The initial evaluation is carried out by estimating the evaluation of the outer model, namely the validity and reliability of each reflective construct. Next is the evaluation of inner models for testing research models using the WarpPLS 4.0 program. The significance of the parameters is determined by resampling bootstrapping and using 500 sub-samples of equal size to that of the original sample. The results and discussion of hypothesis testing show that the self-efficacy of star hotels employees in Bali is able to predict entrepreneurial intention significantly. Self determination can predict entrepreneurial intention of star hotels employees in Bali significantly. Self-identity of star hotel employees in Bali was able to predict entrepreneurial intention insignificantly. Keywords: entrepreneurial behavior, self efficacy, self determination, self identity, entrepreneurial intention JEL Classifications: L26, M21 DOI: https://doi.org/10.32479/irmm.10077